2015
DOI: 10.1080/09583157.2015.1049977
|View full text |Cite
|
Sign up to set email alerts
|

First record ofAspergillus oryzae(Eurotiales: Trichocomaceae) as an entomopathogenic fungus of the locust, Locusta migratoria (Orthoptera: Acrididae)

Abstract: A novel entomopathogenic fungus of L. migratoria was identified as A. oryzae using a comparative sequence analysis of the ITS regions, aflatoxin B1 detection and morphological analysis. The fungus isolated from a dead locust collected in northwestern China was found to be pathogenic to the insect. Phylogenetic experiments revealed a 99% similarity between the fungus and those of three species, A. oryzae, A. flavus and A. parvisclerotigenus which are in the same branch of the Flavi section of the genus A c c e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…Generally, the physiological activities of the animal were normal, which suggests that A. oryzae may not have toxic effects on the rabbits. This agrees with other studies which indicated that A. oryzae and other entomopathogenic fungi have no effect on non-target organisms and are environmentally-friendly (Fernandes and Bittencourt, 2008;Ghany, 2015;Kaaya and Hassan, 2000;Kalsbeek et al, 1995;Stafford and Allan, 2014;Zekeya et al, 2020Zekeya et al, , 2019Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Generally, the physiological activities of the animal were normal, which suggests that A. oryzae may not have toxic effects on the rabbits. This agrees with other studies which indicated that A. oryzae and other entomopathogenic fungi have no effect on non-target organisms and are environmentally-friendly (Fernandes and Bittencourt, 2008;Ghany, 2015;Kaaya and Hassan, 2000;Kalsbeek et al, 1995;Stafford and Allan, 2014;Zekeya et al, 2020Zekeya et al, , 2019Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Our results found that M. anisopliae CQMa421 could effectively infected the adults and nymphs of the pest L. migratoria, suggesting the potential of this fungus for the pest control. Aspergillus oryzae (Eurotiales: Trichocomaceae) was also reported as an entomopathogenic fungus for the control of the locust L. migratoira [48]. The low LT50 of L. migratoria found under concentrations of 1 × 10 7 conidia/ml and 1 × 10 8 conidia/mL indicated high susceptibility of L. migratoria to M. anisopliae infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although Trichocomaceae species are ubiquitous in plant and soil materials [48,49], this fungal family was rarely found in the soil in our study (< 0.63%). Entomopathogenic species are also known in this family [50], suggesting that there may be a parasitic relationship with beetles. However, it is also possible that this group enters scavengers' guts with food resources such as dead carcasses, where they grew prolifically.…”
Section: Discussionmentioning
confidence: 99%